 It is currently 12 Jul 2020, 07:00 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here. # If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for  Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:
Founder  Joined: 18 Apr 2015
Posts: 12066
Followers: 255

Kudos [?]: 3008 , given: 11277

If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for [#permalink]
Expert's post 00:00

Question Stats: 90% (01:05) correct 10% (00:51) wrong based on 10 sessions
If $$f(x) = 2x- 2$$ and $$g(x) = 4 - x$$, then $$f(g(x)) = g(f(x))$$ for which of the following x values?

Indicate all such values.

❑ -2

❑ -1

❑ 0

❑ 1

❑ 2

❑ None of the above
[Reveal] Spoiler: OA

_________________

Need Practice? 20 Free GRE Quant Tests available for free with 20 Kudos
GRE Prep Club Members of the Month: Each member of the month will get three months free access of GRE Prep Club tests.

Founder  Joined: 18 Apr 2015
Posts: 12066
Followers: 255

Kudos [?]: 3008 , given: 11277

Re: If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for [#permalink]
Expert's post
Post A Detailed Correct Solution For The Above Questions And Get A Kudos.
Question From Our New Project: GRE Quant Challenge Questions Daily - NEW EDITION!

_________________

Need Practice? 20 Free GRE Quant Tests available for free with 20 Kudos
GRE Prep Club Members of the Month: Each member of the month will get three months free access of GRE Prep Club tests. Moderator Joined: 16 Oct 2019
Posts: 63
Followers: 0

Kudos [?]: 49  , given: 21

Re: If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for [#permalink]
1
KUDOS
f(g(x)) = 2(g(x))-2 = 2(4-x)-2 = 6-2x
g(f(x)) = 4-(f(x)) = 4-(2x-2) = 6-2x
f(g(x)) = g(f(x)), for any value of x Re: If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for   [#permalink] 31 May 2020, 20:17
Display posts from previous: Sort by

# If f(x) = 2x— 2 and g(x) = 4 — x, then f(g(x)) = g(f(x)) for  Question banks Downloads My Bookmarks Reviews Important topics Powered by phpBB © phpBB Group Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.